1997
DOI: 10.1111/0162-895x.00077
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Threat and Authoritarianism

Abstract: There has been a long history of work on authoritarianism that has looked at the role of societal threat. Much of the empirical research in this tradition has relied on aggregate data to examine the relationship between societal threat and authoritarian attitudes and behaviors. Our analysis uses individual-level data and a range of perceived threat measures to better understand the dynamics of authoritarianism and threat. We also move beyond the hypothesis of a direct relationship between threat and authoritar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
760
1
20

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 817 publications
(855 citation statements)
references
References 21 publications
49
760
1
20
Order By: Relevance
“…4 There is an extensive and important body of work examining the relationship between a variety of political attitudes and other characteristic adaptations. These adaptations include, among others, RWA (e.g., Adorno et al 1950;Altemeyer 1996;Ekehammar et al 2004;Feldman 2003;Feldman and Stenner 1997;Hetherington and Weiler 2009;Stenner 2005), SDO (e.g., Ekehammar et al 2004;Sidanius and Pratto 1999;Sidanius, Pratto, and Bobo 1996), Racial Resentment (e.g., Feldman and Huddy 2005;Henry and Sears 2002;Kinder and Mendelberg 2000;Kinder and Sanders 1996;Kinder and Sears 1981;Sniderman and Carmines 1997), and core values (e.g., Goren 2001Goren , 2005Jacoby 2006). Our work contributes to this research by examining (1) how basic dispositional traits-arguably formed prior to these characteristic adaptations-shape political attitudes (another characteristic adaptation) and (2) how the effects of Big Five traits vary across clearly identified contexts.…”
Section: Dispositional Traits-the Big Fivementioning
confidence: 99%
See 1 more Smart Citation
“…4 There is an extensive and important body of work examining the relationship between a variety of political attitudes and other characteristic adaptations. These adaptations include, among others, RWA (e.g., Adorno et al 1950;Altemeyer 1996;Ekehammar et al 2004;Feldman 2003;Feldman and Stenner 1997;Hetherington and Weiler 2009;Stenner 2005), SDO (e.g., Ekehammar et al 2004;Sidanius and Pratto 1999;Sidanius, Pratto, and Bobo 1996), Racial Resentment (e.g., Feldman and Huddy 2005;Henry and Sears 2002;Kinder and Mendelberg 2000;Kinder and Sanders 1996;Kinder and Sears 1981;Sniderman and Carmines 1997), and core values (e.g., Goren 2001Goren , 2005Jacoby 2006). Our work contributes to this research by examining (1) how basic dispositional traits-arguably formed prior to these characteristic adaptations-shape political attitudes (another characteristic adaptation) and (2) how the effects of Big Five traits vary across clearly identified contexts.…”
Section: Dispositional Traits-the Big Fivementioning
confidence: 99%
“…See also Feldman and Johnston (2009) on the two-dimensional nature of ideology. 6 A related, but distinct literature, addresses the question of whether situational factors (e.g., priming of mortality salience [Landau et al 2004;, personal threat [Feldman and Stenner 1997;Stenner 2005], and emotional cues [Brader 2006;Marcus et al 1995]) affect the importance of individual-level differences (e.g., RWA) in explaining behavior and opinions. and question existing conventions and assumptions.…”
Section: The Big Five and Political Attitudesmentioning
confidence: 99%
“…First, whether authoritarianism is conceptualized as an individual personality trait forged in the crucible of childhood (Adorno et al 1950 ), a socially-learned attitude (Altemeyer 1981(Altemeyer a, 1988(Altemeyer , 1996(Altemeyer , and 2006, or a predisposition (Stenner 2005 ), authoritarians are described as rigid thinkers who perceive the world in black-and-white terms (Adorno et al 1950 ;Altemeyer 1981Altemeyer a, 1988Altemeyer , 1996Duckitt 1989 ;Feldman 2003 ;Feldman and Stenner 1997 ;Hetherington and Weiler 2009 ;Jost et al 2003 ;Lavine et al 2005 ;Stenner 2005 ). Uniformity and order are authoritarian watch words.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Some, though not all, studies suggest that the relation between RWA and negative outgroup attitudes is indeed stronger in situations in which the ingroup is threatened. Using an indirect measure of RWA that was obtained by asking opinions about child-rearing, Feldman and Stenner (1997) showed that various forms of threat activate authoritarianism and that this interacts with perceived threat in the prediction of ethnocentrism. Similarly, Cohrs, Kiehlmann, Maes, and Moschner (2005) found a significant interaction between RWA and perceptions of threat in predicting German internet users' post-9/11 attitudes.…”
Section: Towards An Integrated Perspectivementioning
confidence: 99%